Sceletium tortuosum: A review on its phytochemistry, pharmacokinetics, biological, pre-clinical and clinical activities. (6th April 2022) - Olatunji, T.L.; Siebert, F.; Adetunji, A.E.; Harvey, B.H.; Gericke, J.; Hamman, J.H.; Van der Kooy, F.
Abstract: Ethnopharmacological relevance: Sceletium tortuosum (L.) N.E.Br., the most sought after and widely researched species in the genus Sceletium is a succulent forb endemic to South Africa. Traditionally, this medicinal plant is mainly masticated or smoked and used for the relief of toothache, abdominal pain, as a mood-elevator, analgesic, hypnotic, anxiolytic, thirst and hunger suppressant, and for its intoxicating/euphoric effects. Sceletium tortuosum is currently of widespread scientific interest due to its clinical potential in treating anxiety and depression, relieving stress in healthy individuals, and enhancing cognitive functions. These pharmacological actions are attributed to its phytochemical constituents referred to as mesembrine-type alkaloids. Aim of the review: The aim of this review was to comprehensively summarize and critically evaluate recent research advances on the phytochemistry, pharmacokinetics, biological, pre-clinical and clinical activities of the medicinal plant S. tortuosum . Additionally, current ongoing research and future perspectives are also discussed. Methods: All relevant scientific articles, books, MSc and Ph.D. dissertations on botany, behavioral pharmacology, traditional uses, and phytochemistry of S. tortuosum were retrieved from different databases (including Science Direct, PubMed, Google Scholar, Scopus and Web of Science). For pharmacokinetics and pharmacological effects of S. tortuosum, the focus fell on relevant publications published between 2009 and 2021. Results: Twenty-five alkaloids belonging to four structural classes viz: mesembrine, Sceletium A4, joubertiamine, and tortuosamine, have been identified from S. tortuosum, of which the mesembrine class is predominant. The crude extracts and commercially available standardized extracts of S. tortuosum have displayed a wide spectrum of biological activities (e.g. antimalarial, anti-oxidant, neuromodulatory, immunomodulatory, anti-HIV, neuroprotection) in in vitro or in vivo studies. While the plant has been studied in clinical populations, this has only been in healthy subjects, so that further study in pathological states remains to be done. Nevertheless, the aforementioned studies have demonstrated that S. tortuosum has potential for enhancing cognitive function and managing anxiety and depression. Conclusion: As an important South African medicinal plant, S. tortuosum has garnered many research advances on its phytochemistry and biological activities over the last decade. These scientific studies have shown that S. tortuosum has various bioactivities. The findings have further established the link between the phytochemistry and pharmacological application, and support the traditional use of S. tortuosum in the indigenous medicine of South Africa. Highlights: Sceletium tortuosum is the most widely researched species in the genus Sceletium. This is due to its potential to treat different central nervous system disorders. Mesembrine alkaloids are considered the major bioactive compounds. This review provides a comprehensive update on research advances of S. tortuosum.